A bio-based and non-toxic polyurethane film derived from Luffa cylindrica cellulose and L-Lysine diisocyanate ethyl ester - YÜCE, HÜSEYİN; AKAY, ÖZGE (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This study aims to explore the step-growth polymerization (SGP) between the most abundant biomass-cellulose (LCC) extracted from Luffa cylindrica (LC) and L-Lysine diisocyanate ethyl ester (L-LDI) to be achieved an unprecedented polyurethane network (PUR). The resulting bio-based and non-toxic PUR film is obtained by direct solution casting after SGP. The efficiency of the SGP is examined in detail Fourier transform infrared (FT-IR) and proton nuclear magnetic resonance (H-1 NMR) spectroscopies, water contact angle (WCA) measurements, thermogravimetric and differential scanning calorimetry analyses (TGA and DSC) by comparing precursors and final film. Moreover, the biodegradation behavior of PUR achieved is evaluated in vitro both hydrolytic and enzymatic media. Based on the conducted analyses, PUR film shows higher hydrophobicity and degradation temperatures compared to raw LC and LCC. Moreover, it is determined that the PUR film more degradable than its precursors in both hydrolytic and enzymatic media. Consequently, the approach developed here is broadly adaptable to other functional isocyanate monomers and will be useful to scientists working on bioplastic applications.
Keywords: Biodegradability; Cellulose; Luffa cylindrica; Polyurethane; Step-growth polymerization; BIOMEDICAL APPLICATIONS; FIBERS; SPONGE; ACID; COMPOSITES; BEHAVIOR